Pengaruh Waktu Kontak dan Kecepatan Pengadukan Terhadap Penyerapan Zat Warna Methylene Blue Menggunakan Biosorben Kulit Matoa (Pometia pinnata) - Mufi Nasda; Desy Kurniawati; Edi Nasra (Periodic, 2023)
Methylene blue is an aromatic hydrocarbon compound or thiazine dye with the chemical formula C16H18N3SCl which is most often used in industry, this cationic dye is very dangerous with a threshold value ranging from 5-10 mg/L in water and is difficult to degrade in the environment because it contains benzene compounds. The purpose of this study was to reduce the impact of methylene blue pollution on the waters. The adsorption method was selected in batches by utilizing plantation waste from matoa fruit peel as an adsorbent in the absorption of MB waste, because it is more effective, inexpensive, and environmentally friendly. Matoa skin contains cellulose and lignin, so it is considered potential to be used as an adsorbent. The results showed that the matoa skin adsorbent was able to adsorb methylene blue dye at an optimum contact time of 120 minutes and a stirring speed of 200 rpm, which was measured using aÂ UV-Vis spectrophotometer at a wavelength of 664 nm.